Oxidative dehalogenation of trichlorophenol catalyzed by a promiscuous artificial heme-enzyme. Issue 21 (4th May 2022) - Zambrano, Gerardo; Sekretareva, Alina; D'Alonzo, Daniele; Leone, Linda; Pavone, Vincenzo; Lombardi, Angela; Nastri, Flavia
Abstract : The artificial metalloenzyme FeMC6*a is able to perform the H2 O2 -mediated dechlorination of 2, 4, 6-trichlorophenol with unrivalled catalytic efficiency, highlighting its potential application for the removal of toxic pollutants. Abstract : The miniaturized metalloenzyme Fe(iii )-mimochrome VI*a (Fe(iii )-MC6*a) acts as an excellent biocatalyst in the H2 O2 -mediated oxidative dehalogenation of the well-known pesticide and biocide 2, 4, 6-trichlorophenol (TCP). The artificial enzyme can oxidize TCP with a catalytic efficiency ( k cat / K TCPm = 150 000 mM −1 s −1 ) up to 1500-fold higher than the most active natural metalloenzyme horseradish peroxidase (HRP). UV-visible and EPR spectroscopies were used to provide indications of the catalytic mechanism. One equivalent of H2 O2 fully converts Fe(iii )-MC6*a into the oxoferryl-porphyrin radical cation intermediate [(Fe(iv )O)por˙ + ], similarly to peroxidase compound I (Cpd I). Addition of TCP to Cpd I rapidly leads to the formation of the corresponding quinone, while Cpd I decays back to the ferric resting state in the absence of substrate. EPR data suggest a catalytic mechanism involving two consecutive one-electron reactions. All results highlight the value of the miniaturization strategy for the development of chemically stable, highly efficient artificial metalloenzymes as powerful catalysts for the oxidative degradation of toxic pollutants.